Profile of Brazilian Under-19 Volleyball Team Athletes: Anthropometry, Jump Performance, Stiffness and Pre-Stretch Augmentation Percentage - Guilherme Berriel; Ananda Silveira Cardoso; Maria Eduarda Cavagni; Luiz Fernando Kruel; Leonardo Alexandre Peyré-Tartaruga (International Journal of Sports Physical Therapy)
# Introduction